2009
DOI: 10.1136/adc.2008.144014
|View full text |Cite
|
Sign up to set email alerts
|

Dyskinetic cerebral palsy in Europe: trends in prevalence and severity

Abstract: The prevalence of dyskinetic cerebral palsy appears to have increased in children with a normal birth weight. They have frequently experienced perinatal adverse events. Most children have a severe motor impairment and several accompanying impairments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
121
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(130 citation statements)
references
References 25 publications
7
121
2
Order By: Relevance
“…A recent study, also based on the SCPE common database, reported a significant increase in the prevalence of dyskinetic CP among NBW children for the period 1976-1984, followed by a plateau. [35] Our analysis covered a later period, 1980-1998, and confirmed the leveling off of prevalence of dyskinetic CP.…”
Section: Discussionsupporting
confidence: 74%
“…A recent study, also based on the SCPE common database, reported a significant increase in the prevalence of dyskinetic CP among NBW children for the period 1976-1984, followed by a plateau. [35] Our analysis covered a later period, 1980-1998, and confirmed the leveling off of prevalence of dyskinetic CP.…”
Section: Discussionsupporting
confidence: 74%
“…[13][14][15] Dystonia is more prevalent than the choreoathetotic subtype 19 and commonly manifests as dystonic hyper tonia of the upper extremities, neck, and face with concomitant * The Activa RC neurostimulator system was used in all cases. Lead location was calculated in reference to the midpoint of the anterior commissureposterior commissure (AC-PC) line.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with the more common spastic CP, the dyskinetic forms have greater motor impairment and functional disability, 15 resulting in significant long-term morbidity and caretaker burden. And although this dystonic group has responded only modestly to DBS, 1,16,22,24,27,36 even subtle improvements can significantly impact quality of life and caretaking, 24,27,36 thus underscoring the importance of strict adherence to established classification schemes to identify patients who will benefit most.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The athetotic type of cerebral palsy (known as dyskinetic in Europe) represents 6-15% of all cases of CP, and tends to have a clinically severe prognosis (1)(2)(3). However, a definitive diagnosis of delayed or aberrant motor progress and differentiation between athetosis and spasticity are not always straightforward until children become old enough for a full examination of functional outcomes (3)(4)(5).…”
Section: Introductionmentioning
confidence: 99%